2012
DOI: 10.1007/s00221-012-3097-5
|View full text |Cite
|
Sign up to set email alerts
|

How perceived egocentric distance varies with changes in tonic vergence

Abstract: According to the eye muscle potentiation (EMP) hypothesis, sustained vergence leads to changes in egocentric perceived distance. This perceptual effect has been attributed to a change in the resting or tonic state of vergence. The goal of the present study was to test the EMP hypothesis by quantifying the relationship between prism-induced changes in tonic vergence and corresponding changes in perceived distance and by measuring the dynamics of changes in perceived distance. During a 10-min exposure to 5-diopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Indeed, efferent copies of vergence movements, proprioception on convergence state (Priot et al, 2012), or simply disparity indices on which vergence movement can be programmed (Ziegler and Hess, 1997) are all candidates to be involved in our ability to assess depth. Conversely, our understanding of the 3D space can trigger movements in accordance with our perception.…”
Section: Improving Visual Perception and Awarenessmentioning
confidence: 99%
“…Indeed, efferent copies of vergence movements, proprioception on convergence state (Priot et al, 2012), or simply disparity indices on which vergence movement can be programmed (Ziegler and Hess, 1997) are all candidates to be involved in our ability to assess depth. Conversely, our understanding of the 3D space can trigger movements in accordance with our perception.…”
Section: Improving Visual Perception and Awarenessmentioning
confidence: 99%
“…As such, motor efference and/or proprioception from the vergence system are considered as sources of information for distance perception (Brenner and Van Damme, 1998). It was found that changes in vergence state using prismatic deviation consistently altered the way observers judged distance (Tresilian et al, 1999; Priot et al, 2012). Studies typically suggest that oculomotor cues to distance are only efficient in the near space, and notably in impoverished scenes (Kunnapas, 1968; Tresilian et al, 1999).…”
Section: Introductionmentioning
confidence: 99%